Awareness about breast cancer among women attending obstetrics and gynaecology department in a tertiary care hospital of Jharkhand, India - Kumar, Mithilesh; Kashyap, Vivek (International Journal Of Community Medicine And Public Health, 2017)
Background: Most of the patients of breast cancer seek medical advice when the disease is fairly advanced. Lack of awareness about the risk factors and symptoms of the disease is the main cause of late detection of this cancer- at a stage that they can no more be cured. The objective was to determine the awareness about breast cancer among women attending obstetrics and gynaecology department of Rajendra Institute of Medical Sciences (RIMS), Ranchi. Methods: It was a descriptive, cross sectional hospital based study conducted in Obstetrics and Gynaecology department of RIMS, Ranchi between January to March 2015 among women aged more than 15. A total of 162 women selected by consecutive sampling were interviewed using a pretested semi-structured questionnaire after taking informed consent. Data entry was done in MS excel and analyzed in SPSS software. Frequency distribution was done and chi square test was used to find the association between awareness of breast cancer with different socio-demographic profile. Results: Mean age of the participants was 30.15±10.54. Out of total 162 participants, 123 (75.9%) had heard about breast cancer. 72 (58.5%) of the participants had knowledge of breast cancer from friends and neighborhood. 46.4% of the participants were aware of at least one of the symptoms of breast cancer. 66 (53.6%) of the participants thought family history was the cause for breast cancer. 17 (13.8%) of the participants were aware of breast self-examination and 4 participants had ever done it. Awareness of breast cancer was significantly associated with education, ethnicity, and residence of the participants. Conclusion: there was low level of awareness about breast cancer in the study population. There is a need for programs for increasing awareness regarding breast cancer for correct knowledge and its early detection.